Osteopontin-targeted probe detects orthotopic breast cancers using optoacoustic imaging. (17th November 2018) - Samykutty, A.; Thomas, A.; McNally, M.; Chiba, A.; McNally, L. R.
ABSTRACT: Improved detection of breast cancer using highly sensitive, tumor-specific imaging would facilitate diagnosis, surveillance and assessment of response to treatment. We conjugated osteopontin peptide to an infrared fluorescent dye to serve as a contrast agent for detection of breast cancer by multispectral optoacoustic tomography (MSOT). Selective binding of the osteopontin-based probe was identified using flow cytometry and near infrared fluorescent imaging in triple negative and HER2 positive breast cancer cell lines in vitro. Osteopontin-750 accumulation was evaluated in vivo using MSOT with secondary confirmation of signal accumulation using near infrared fluorescent imaging. The osteopontin-based probe demonstrated binding to breast cancer cells in vitro. Similarly, after intravenous administration of the osteopontin-750 probe, it accumulated preferentially in the subcutaneous breast tumor in nude mice (557 MSOT a.u. compared to untargeted organs such as kidney (53.7 MSOT a.u.) and liver (32.1 MSOT a.u.). At 2.5 h post-injection, signal intensity within the tumor was 9.7 and 17 times greater in the tumor bed than in the kidney or liver, respectively. Fluorescence imaging ex vivo comparing tumor signal to that of nontarget organs confirmed the results in vivo. MSOT imaging demonstrated selective accumulation of the fluorescent osteopontin targeting probe to tumor sites both in vitro and in vivo, and provided high-resolution images. Further development of this tool is promising for advanced diagnostic imaging, disease surveillance and therapeutic models that limit nontarget toxicity.